Complete genome sequence and description of Lactococcus garvieae M14 isolated from Algerian fermented milk. (March 2016) - Moumene, M.; Drissi, F.; Croce, O.; Djebbari, B.; Robert, C.; Angelakis, E.; Benouareth, D.E.; Raoult, D.; Merhej, V.
Abstract: We describe using a polyphasic approach that combines proteomic by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF) analysis, genomic data and phenotypic characterization the features of Lactococcus garvieae strain M14 newly isolated from the fermented milk (known as raib) of an Algerian cow. The 2 188 835 bp containing genome sequence displays a metabolic capacity to form acid fermentation that is very useful for industrial applications and encodes for two bacteriocins responsible for its eventual bioprotective properties.